Inquiries of deaths under the Malaysian Criminal Procedure Code - Kamarudin, Abdul Rani (IIUM Press, 2009)
This paper deals with cases of any sudden death or unnatural death or death by violence or of any person being found dead without its being known how that person died. It discusses among others, on the requirement to inform the relevant authorities especially the police, the manner of investigation to be conducted and whether a post mortem of the deceased is required or not. It also looks at the nature of the inquiry, the powers given to the Magistrates in ascertaining the cause of death, the rules of evidence and the procedure involve. The powers of the Public Prosecutor and the role of the pathologist in relation to the death of the person are also discussed